Bis(sulfanediyl)bis(6-aminopyrimidin-4-ones): Versatile precursors for novel bis(sulfanediyl)bis(tetrahydropyrimido[4, 5-b]quinoline-4, 6-diones) linked to aliphatic spacer via multi-component reactions. Issue 13 (3rd July 2021) - Diab, Hadeer M.; Salem, Mostafa E.; Elwahy, Ahmed H. M.; Abdelhamid, Ismail A.
Abstract: A synthesis of novel bis (sulfanediyl) bis (tetrahydropyrimido[4, 5- b ]quinoline-4, 6-diones), linked to aryl, heteroaryl, and spirocyclic-oxindole moieties at position-5, as novel hybrid molecules was reported. 2, 2'-(Butane-1, 4-diyl bis (sulfanediyl)) bis (6-aminopyrimidin-4(1 H )-one) was utilized as a precursor to our target compounds via a multicomponent reaction with two equivalents of both of the appropriate aldehyde and dimedone. The target compounds were alternatively obtained by bis -(alkylation) of the appropriate 5-aryl-2-thioxohexahydropyrimido[4, 5- b ]quinoline-4, 6-dione with 1, 4-dibromobutane in moderate basic medium. Graphical Abstract: UF0001